Distribution and mass load of per- and poly-fluoroalkyl substances (PFAS) in the sediments of a shallow urbanised marine embayment in south-eastern Australia - Navneet Singh; Matthew P.J. Askeland; Timothy L. Coggan; David M. Kennedy; Oliver A.H. Jones (Marine Environmental Research, 2026)

Diet selection of sympatric marine turtles reveals the importance of diverse benthic habitats - Alexa R. Putillo-Wehry; Simona A. Ceriani; Sue Murasko; Stephanie V. Gkionis; Sandra Chupinsky; Timothy W. Jones; Katherine Suchanec; Mariana M. P. B. Fuentes (Marine Biology, 2026)

Fraction-specific pathways of sulfur cycling in agroecosystems with highly weathered soils - Wenxiang Zhou; Brigid A. McKenna; Timothy I. McLaren; Ram C. Dalal; Joshua Bennett-Jones; Peter M. Kopittke (Agriculture, Ecosystems & Environment, 2026)

Towards a European small-scale fishing vessel tracking programme: Overview, challenges and opportunities - Tania Mendo; Anna Mujal-Colilles; Einar Hjorleifsson; Pamela Lattanzi; Luca Marsaglia; Mark James; Marta M. Rufino; Helen Holah; Oliver Tully; Jose Rodriguez-Gutierrez; Patrik Jonsson; Estanis Mugerza; et al. (Marine Policy, 2026)

Palaeowildfire regimes and their palaeoenvironmental significance during the Middle Jurassic of the Ordos Basin - Jiamin Zhou; Longyi Shao; Timothy P. Jones; Man Huang; Langlang Wang; Xiaotao Xu; Xiaoyun Yan; Jing Lu (Science China Earth Sciences, 2026)

Contrasting life‐history strategies of three sympatric icefish species in the northern Scotia Sea - Huw W. James; Timothy Jones; Fabrice Stephenson; Philip R. Hollyman; William D. K. Reid; Martin A. Collins (Journal of Fish Biology, 2026)
Comprehending a species' life‐history strategies is crucial to inform effective conservation efforts. Commercial fishing impacts icefish (family: Channichthyidae) in the Scotia Sea, but detailed information on species‐specific life histories remains largely unknown. In this study, the demographic characteristics of mackerel icefish ( Champsocephalus gunnari ), blackfin icefish ( Chaenocephalus aceratus ) and South Georgia icefish ( Pseudochaenichthys georgianus ) were examined and used to compare inferred life‐history strategies, using long‐term data from demersal and plankton trawl surveys conducted across the South Georgia and the Shag Rocks continental shelves. The results indicated that C. gunnari may exhibit alternative reproductive tactics, as they appear to spawn multiple times in a single year and mature at varying sizes. Conversely, C. aceratus and P. georgianus reproduced once per annum and appeared to favour investing in somatic growth, resulting in them consistently maturing at a larger size. Seasonal sex ratios demonstrated a reduction in captured mature males for C. aceratus and P. georgianus during the suspected spawning period, supporting the hypothesis of sex‐specific behavioural patterns during the reproductive period. These findings highlight the variation in the life‐history strategies among these three icefish species, which should be considered during the development of future management measures.

Lynch syndrome integrative epidemiology and genetics (LINEAGE): rationale for cohort design - Swati G. Patel; Holli A. Loomans-Kropp; Zachariah H. Foda; Bryson W. Katona; Suzi Birz; Carol A. Burke; Jordan Clawson; Brian Furner; Camille Hochheimer; Elizabeth Magnan; Luigi Ricciardiello; Harminder Singh; et al. (Familial Cancer, 2026)

Effect of unstable surface during loaded-inspiratory task on diaphragm and trunk muscle activity in stroke patients - Fang Liu; Alice Y. M. Jones; Raymond C. C. Tsang; Timothy T. T. Yam; William W. N. Tsang (European Journal of Applied Physiology, 2026)

A diagenetic shale source for lithium in oilfield brines: Insights from the Devonian Bakken–Three Forks system, Williston Basin - Kyle M. Henderson; Anthony E. Williams-Jones; Swapan Sahoo; Chunqing Jiang; Timothy O. Nesheim (Chemical Geology, 2026)

Investigating the Impact of Blunt Force Trauma: A Probabilistic Study of Behind Armor Blunt Trauma Risk - Vivek Bhaskar Kote; Lance L. Frazer; Zachary S. Hostetler; Derek A. Jones; Matthew Davis; Joost Op’t Eynde; Jason Kait; Derek Pang; Dale Bass; Jared Koser; Alok Shah; Narayan Yoganandan; et al. (Annals of Biomedical Engineering, 2026)

Distribution and ecology of the four Macrourus species by‐caught in the longline fishery at South Georgia, Southern Ocean - José Abreu; Philip R. Hollyman; Jennifer J. Freer; M. L. Romero Martínez; José P. Queirós; Timothy Jones; Richard A. Phillips; José C. Xavier; Martin A. Collins (Journal of Fish Biology, 2026)
Although Macrourus species are the main by‐catch across Southern Ocean longline fisheries, including around South Georgia, the lack of species‐specific data has hindered effective management and ecological understanding. Aggregation of macrourids at genus level masks critical interspecific differences in life‐history strategies and vulnerabilities to fishing. Here, we provide the first comprehensive biological assessment of the four macrourid species caught in South Georgia waters: Macrourus caml , Macrourus carinatus , Macrourus holotrachys and Macrourus whitsoni . Using fishery and observer data collected in 2018–2022, we reveal pronounced female‐biased sex ratios in three species ( M. holotrachys , M. carinatus and M. caml ), strong depth‐based segregation by body length, distinct distributions and habitat preferences related to environmental features (bathymetric depth and slope, primary productivity and temperature). By‐catch rates were highest in the southern region of South Georgia and varied across species: M. holotrachys was the most frequently caught and had a wide spatial and bathymetric distribution (∼1000–1750 m); M. caml was the second most caught and appeared the most flexible in terms of habitat use; M. carinatus was mainly caught in the west, including at Shag Rocks; and M. whitsoni was caught less frequently and in deeper water (> 1500 m), mostly in the northeast and east, and had the most restricted distribution. These interspecific differences underscore the need for species‐level assessments of fisheries risk and improved data collection to fill knowledge gaps. Overall, this study provides a critical foundation for understanding the ecology of Macrourus species in sub‐Antarctic ecosystems and highlights that additional data are required for by‐caught species to aid species‐level management in toothfish longline fisheries in the CCAMLR area.

Multi-species aggregation and movement patterns of danaid butterflies (Nymphalidae: Danainae) in Hong Kong - Yuet Fung Ling; Emily E. Jones; Nicole Yu; Kirsten Boehm; Long In Cheung; Chun Hoi Law; Even Y. M. Leung; Megan Mei Yan Low; Rui Wang; Wing Kwong Yau; Sui Fai Hydrogen Pun; Yuk Lin Colleen Chiu; et al. (Journal of Insect Conservation, 2026)
Danaid butterflies (Nymphalidae: Danainae) in Asia form seasonal aggregations and/or exhibit migratory flights similar to those of the North American monarch ( Danaus plexippus ). In contrast to this well-studied single-species system, however, Asian danaids form smaller multi-species aggregations and show seasonal movements which remain relatively understudied. In this study, we used publicly reportable stickers to tag 15,918 danaid butterflies from 13 species and five genera ( Euploea , Tirumala , Danaus , Ideopsis , Parantica ) over four years in Hong Kong to elucidate patterns of seasonal aggregation and movements. Species assemblages were distinct at forested valley habitats versus open sites rich in pyrrolizidine alkaloid (PA) plants. Using mark-recapture, we estimated up to 16,000 butterflies in a single aggregation. Recoveries of 1,503 tags (50.6% reported by the public) revealed local movements of 78 individuals, but no butterflies were reported outside Hong Kong. The observed variation in aggregation dynamics and movement patterns indicate interspecific differences in site selection, overwintering strategies, and orientation of seasonal movement. Regional collaboration across southern China and the Indochinese region is necessary to understand these complicated patterns and inform the conservation of sensitive overwintering and migratory phenomena. Implications for insect conservation Aggregation and migration of Asian danaid butterflies may be similarly vulnerable to habitat and climate changes that have led to extensive declines in the migratory monarchs in North America. Our study highlights the need for dynamic and comprehensive conservation strategies that adequately consider the requirements of many species involved in the multi-species danaid systems in tropical and subtropical Asia.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Multi-proxy records of wildfires and climate-vegetation-wildfire interactions during the Middle Jurassic of the Santanghu Basin, northwest China - Jiamin Zhou; Longyi Shao; Timothy P. Jones; Yangyang Huang; Mengran Chen; Yuedong Ma; Jing Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Functional group composition of soil organic carbon varies between soil organic matter fractions but not with long-term cropping or soil depth - Wenxiang ZHOU; Brigid A. MCKENNA; Joshua BENNETT-JONES; Timothy I. MCLAREN; Ram C. DALAL; Peter M. KOPITTKE (Pedosphere, 2025)

Sorption dynamics of six per- and polyfluoroalkyl substances in estuarine sediments: The role of particle size distribution and salinity in low organic carbon sediments - Navneet Singh; Matthew P.J. Askeland; Timothy L. Coggan; Oliver A.H. Jones (Environmental Pollution, 2025)

Spatial and Temporal Variation in Wave Overtopping Across a Coastal Structure Based on One Year of Field Observations - Jennifer Brown; Gerd Masselink; Margaret Yelland; Christopher Stokes; Timothy Poate; Robin Pascal; David Jones; John Walk; Christopher Cardwell; Barry Martin; Peter Ganderton; Julie Gregory; et al. (Journal of Marine Science and Engineering, 2025)
Coastal managers worldwide must prepare for changes in annual wave overtopping events due to climate change and sea-level rise. Research often assesses overtopping discharges by extreme events at a sea wall crest, typically using data from physical models or empirical rules based on scaled experiments. Here, we analyse a unique 1-year field dataset of coastal wave overtopping, from SW England, to determine the number of individual waves, regardless of their size, overtopping two locations across a coastal structure. The coastal conditions causing the most frequent overtopping differ from those driving it landward, complicating hazard communications for multiuse infrastructure. These data are the first field observations covering a year of tide, wave and wind conditions that cause overtopping of a vertical sea wall. Storms have a minimal (

Multi-proxy records of wildfires and climate-vegetation-wildfire mechanisms during the Middle Jurassic of the Yili Basin, Northwest China - Jiamin Zhou; Longyi Shao; Timothy P. Jones; Yangyang Huang; Mengran Chen; Jing Lu; Jason Hilton (Global and Planetary Change, 2025)

Biostratigraphic and sequence stratigraphic study of the Late Cretaceous-Paleogene succession in the Anambra Basin, southeastern Nigeria: Insights from the Amama-1 and Bara-1 wells - Joy Obiageli Njoku; Timothy Chibuike Anyanwu; Diugo Okereke Ikoro; Geoffrey Chijioke Soronnadi-Ononiwu; Jones Edward Acra; Emeka Austin Okoli; Chidiebere Charles Agoha (Journal of African Earth Sciences, 2025)

Assessing shifting technology in genetic monitoring of the North American plains bison Federal conservation herds - Shawna J. Zimmerman; Rachael Giglio; Chris Geremia; Lee Jones; Blake McCann; Timothy J. Smyser; Brendan J. Moynahan; Sara J. Oyler-McCance (Conservation Genetics, 2025)
Human expansion is a major driver of both declining wildlife abundance and the contraction of species’ distributions, increasing the risk of genetic erosion and the need for genetic monitoring. Rapidly advancing technology has expanded the types of genetic data that are available for wildlife conservation. However, inferences from different genetic markers could result in different management decisions and, thus, must be considered carefully. Rebounding from near extinction in the early 1900s, the majority of North American plains bison ( Bison bison bison ) are managed as small and isolated herds. Microsatellite-based analyses have been used to inform management of the US Federal bison conservation herds since the early 2000s. Transitioning from monitoring with tens of multiallelic loci (e.g., microsatellite loci) to thousands of biallelic loci (e.g., single nucleotide polymorphisms [SNPs]) could increase genotyping efficiency and improve the precision of population genetic inference but would require an understanding of the inferential differences between genetic marker types. We compared microsatellite-based measures of genetic diversity, differentiation, and population structure for 20 bison conservation herds (17 Federal, 1 Tribal, 2 Canadian) to inference from SNP-based analyses for the Tribal herd and 15 of the Federal herds. Data from both genetic marker types found that all herds have remarkably high genetic diversity given the severity of the bottleneck from which these populations recovered, and that population structure was consistent with founding histories. Importantly, SNPs had greater power to describe differences in genetic diversity and groups of related herds, but only if analyses are based on 250 or more loci. Overall, we found that microsatellite and SNP data can provide comparable conservation insight, but SNPs must be carefully selected to ensure continuity in genetic monitoring and to achieve the increased precision in genetic diversity and differentiation among herds that we observed in this study.

The Impact of Exposure Dosage and Host Genetics on the Shedding Kinetics of Flavobacterium psychrophilum in Rainbow Trout - Darbi R. Jones; Jeremy Everson; Timothy D. Leeds; Gregory D. Wiens; Andrew R. Wargo (Journal of Fish Diseases, 2025)
Flavobacterium psychrophilum , the causative agent of bacterial cold water disease (BCWD), is one of the leading pathogens in rainbow trout ( Oncorhynchus mykiss ) aquaculture. To date, there is little knowledge of the transmission kinetics of F. psychrophilum over the course of infection. In particular, how transmission is affected by host genotype and pathogen exposure dosage are not well studied. In order to fill in these knowledge gaps, we exposed two divergently selected lines of rainbow trout (ARS‐Fp‐R and ARS‐Fp‐S) to a range of dosages of F. psychrophilum (strain CSF117‐10). We then measured mortality and bacterial shedding to estimate transmission risk at multiple time points since initial infection. As dosage increased, the number of fish shedding and the amount of bacteria shed increased ranging from 0% to 100% and 10 3 to 10 8 cells fish −1 h −1 , respectively. In addition, we found that disease resistance (survival) was not correlated with transmission risk blocking, in that 67% of fish which shed bacteria experienced no clinical disease. In general, fish mortality began on Day 3, peaked between Days 5–7 and was higher in the ARS‐Fp‐R line. Results from this study could be used to develop epidemiological models and improve disease management, particularly in the context of aquaculture and selective breeding.

Effects of Sulphate‐Reducing Bacteria Mixed‐Species Biofilms on Microbiologically Influenced Corrosion - Liam Jones; Maria Salta; Torben Lund Skovhus; Kathryn Thomas; Timothy Illson; Julian Wharton; Jeremy Webb (Environmental Microbiology, 2025)
Sulphate reducing prokaryotes are widely acknowledged as key contributors to microbiologically influenced corrosion in industry. Characterisation of their behaviour within mixed‐species biofilms that reflect ecologically relevant conditions is limited. A novel dual anaerobic biofilm reactor protocol allowed a complex microbial consortium to be investigated. Continual biofilm growth resulted in significantly greater corrosive pit density, with 15 and 47 pits mm −2 in the biotic reactor for as received (AR) and polished (P) coupons respectively. There was an average pit density of 3 pits mm −2 in the abiotic reactor for both AR and P coupons. Moreover, a greater pit depth and size were observed when compared to the sterile abiotic conditions. Identifying and understanding the relative contributions of different microbial mechanisms within mixed‐species biofilms is critical. Importantly, electroactive and corrosive Desulfovibrio desulfuricans and Desulfovibrio vulgaris were identified within the biofilm. These microorganisms play a crucial role in extracellular electron transfer, a key process in microbiologically influenced corrosion. The protocol not only deepens the mechanistic understanding of MIC but also offers a versatile tool for testing mitigation strategies under realistic and customizable conditions. This integrated approach can ultimately support the development of more targeted, sustainable corrosion prevention and management practices.

Correction to: Angiotensin II Type 2 Receptor Agonism Alleviates Progressive Post‑stroke Cognitive Impairment in Aged Spontaneously Hypertensive Rats - Abdulkarim Alshammari; Bindu Pillai; Pradip Kamat; Timothy W. Jones; Asamoah Bosomtwi; Mohammad Badruzzaman Khan; David C. Hess; Weiguo Li; Payaningal R. Somanath; Mohammed A Sayed; Adviye Ergul; Susan C. Fagan (Translational Stroke Research, 2025)

Angiotensin II Type 2 Receptor Agonism Alleviates Progressive Post-stroke Cognitive Impairment in Aged Spontaneously Hypertensive Rats - Abdulkarim Alshammari; Bindu Pillai; Pradip Kamat; Timothy W. Jones; Asamoah Bosomtwi; Mohammad Badruzzaman Khan; David C. Hess; Weiguo Li; Payaningal R. Somanath; Mohammed A. Sayed; Adviye Ergul; Susan C. Fagan (Translational Stroke Research, 2025)

Condition assessment and best-practice handling guidelines for skate (Rajiformes) bycatch: Lessons from demersal longline fisheries in the Southern Indian Ocean - Johanna Faure; Clara Péron; Rob Jones; Michael Grima; Colette Appert; Nicolas Gasco; Timothy Lamb; Philippe Ziegler; Jaimie Cleeland (Fisheries Research, 2025)

Compressibility and permeability of flocculated microalgal sediment in filtration-permeation - Jincheng Wu; Neil Cagney; Gerald H. Meeten; Timothy G.J. Jones; Edo S. Boek (Journal of Water Process Engineering, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Concentrations of per- and polyfluoroalkyl substances in estuarine systems can vary greatly within tidal cycles - Navneet Singh; Jorge Paz-Ferreiro; Matthew P.J. Askeland; Timothy L. Coggan; Oliver A.H. Jones (Science of The Total Environment, 2025)

Ten Pressing Questions (and Answers) About Marine Fungi and Opportunities for Collaborations in the Ocean Sciences - Anthony Amend; Nina Gunde-Cimerman; Marco Coelho; Colleen Durkin; Cassandra Ettinger; Hugh Gifford; Amy Gladfelter; Cene Gostinčar; Lior Granit; Igor Grigoriev; Marcelo Gutiérrez; KJE Hickman; et al. (Oceanography, 2025)
Nearly 200 years have passed since the first marine fungus, collected from the shores of North Africa, was described. In that time, marine mycologists have continued to observe, describe, and study fungi in every marine ecosystem examined. Nevertheless, fungi remain functionally “dark matter” of the ocean, presenting a grand opportunity to unravel their roles in ecosystem processes. This report outlines the discussion among participants of the second occasional meeting of marine mycologists at Asilomar, California, in March 2024, in which a diverse and interdisciplinary consortium of researchers enumerated the most pressing, and often basic, unanswered questions in marine fungi. We report on the questions facing the field of marine mycology, identify challenges in addressing those questions, and propose concrete and practical solutions for obtaining their answers. A common thread is the need for increasing cross talk and collaboration between mycologists and oceanographers that would present opportunities for readers to participate in a rapidly growing field.

Plasticity syndromes in wild vertebrates: Patterns and consequences of individual variation in plasticity across multiple behaviours - Erik Johansson; P. Dee Boersma; Timothy Jones; Briana Abrahms (Ecology Letters, 2024)
Behavioural plasticity is an important mechanism allowing animals to cope with changing environments. Theory has hypothesized the existence of ‘plasticity syndromes’—positive correlations in plasticity across multiple behaviours within an individual—affording a generalized ability to respond to environmental change. However, the occurrence of correlated plasticities and their potential fitness consequences in natural populations remain untested. Using a 40‐year dataset on free‐ranging Magellanic penguins, we find evidence of both positively and negatively correlated behavioural plasticities. Plasticity did not strongly affect lifetime reproductive success, but its effect on interannual performance varied significantly by environmental context: plasticity reduced success in average oceanic conditions, increased success in anomalously productive conditions and, contrary to expectation, did not buffer against anomalously unproductive conditions. Such results highlight the complex patterns and consequences of plasticity across behaviours, individuals and environments, and the context‐dependent role that correlated plasticities play in the adaptive capacity of populations to environmental change.

Mechanisms of inertinite enrichment in Jurassic coals: Insights from a Big Data-driven review - Jiamin Zhou; Longyi Shao; Timothy P. Jones; Yangyang Huang; Mengran Chen; Haihai Hou; Jing Lu; Jason Hilton (Earth-Science Reviews, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Rock fishways: Natural designs for an engineered world - Ivor G. Stuart; Timothy J. Marsden; Matthew J. Jones; Matt T. Moore; Lee J. Baumgartner (Ecological Engineering, 2024)

ACPSEM position paper: recommendations for a digital general X-ray quality assurance program - Timothy Ireland; Amanda Perdomo; Kam L. Lee; Adam Jones; Peter Barnes; Thomas Greig; Susan E. Reynolds (Physical and Engineering Sciences in Medicine, 2024)
This guideline has been prepared by the ACPSEM to provide a standardised quality assurance program to be used within General X-ray imaging environments. The guideline includes the responsibilities of various multidisciplinary team members within medical imaging facilities. It must be noted that the listed tests and testing frequencies are not intended to replace or become regulatory requirements. Implementing a quality assurance program as outlined in this position paper is there to ensure best practice for imaging facilities by providing a framework to establish and monitor correct equipment performance. The current document has been produced through an extensive review of current international practices and local experience within the Australasian healthcare environment. Due to the constant evolution of digital radiographic equipment, there is no current consensus in international quality assurance guidelines as they continue to be adapted and updated. This document describes the current state of the use of digital General X-ray equipment in the Australasian environment and provides recommendations of test procedures that may be best suited for the current medical imaging climate in Australasia. Due to the everchanging developments in the medical imaging environment and the ability of new technologies to perform more complex tasks it is believed that in the future this document will be further reviewed in the hopes of producing a more globally agreed upon standard quality assurance program. Any such adjustments that are deemed to be necessary to Version 1.0 of this document will be provided in electronic format on the ACPSEM website with a notification to all parties involved in the use of digital General X-ray equipment. This guideline does not provide detailed methodologies for all the quality control tests recommended as it is it is expected that the professionals implementing aspects of this quality assurance program have the working knowledge and access to appropriate resources to develop testing methodologies appropriate for their local imaging environment.

The deglacial history of 79N glacier and the Northeast Greenland Ice Stream - David H. Roberts; Timothy P. Lane; Richard S. Jones; Michael J. Bentley; Christopher M. Darvill; Angel Rodes; James A. Smith; Stewart S.R. Jamieson; Brice R. Rea; Derek Fabel; Delia Gheorghiu; Allan Davidson; et al. (Quaternary Science Reviews, 2024)

Inertinite in coal and its geoenvironmental significance: Insights from AI and big data analysis - Longyi Shao; Jiamin Zhou; Timothy P. Jones; Fanghui Hua; Xiaotao Xu; Zhiming Yan; Haihai Hou; Dongdong Wang; Jing Lu (Science China Earth Sciences, 2024)

The impact of frequent wildfires during the Permian–Triassic transition: Floral change and terrestrial crisis in southwestern China - Fanghui Hua; Longyi Shao; Xuetian Wang; Timothy P. Jones; Tianchang Zhang; David P.G. Bond; Zhiming Yan; Jason Hilton (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Australian non-perennial rivers: Global lessons and research opportunities - Margaret Shanafield; Melanie Blanchette; Edoardo Daly; Naomi Wells; Ryan M. Burrows; Kathryn Korbel; Gabriel C. Rau; Sarah Bourke; Gresley Wakelin-King; Aleicia Holland; Timothy Ralph; Gavan McGrath; et al. (Journal of Hydrology, 2024)

Nitrate exposure from drinking water and dietary sources among Iowa farmers using private wells - Timothy G. Skalaban; Darrin A. Thompson; Jessica M. Madrigal; Benjamin C. Blount; Maria Morel Espinosa; Dana W. Kolpin; Nicole C. Deziel; Rena R. Jones; Laura Beane Freeman; Jonathan N. Hofmann; Mary H. Ward (Science of The Total Environment, 2024)

Quantifying exposure biases in early instrumental land surface air temperature observations - Emily J. Wallis; Timothy J. Osborn; Michael Taylor; Philip D. Jones; Manoj Joshi; Ed Hawkins (International Journal of Climatology, 2024)
Exposure biases are a pervasive non‐climatic change in land air temperature records which have been introduced as a result of changes in the way thermometers were sheltered from solar radiation and the elements over time. Exposure biases have not been widely accounted for in observational records, due to difficulties detecting/correcting the bias using traditional homogenisation techniques; therefore, exposure biases still contribute significant uncertainty to the early period in global temperature compilations. Here, an empirical approach to address the bias arising from the introduction of Stevenson‐type screens from the late‐19th century is presented. The approach consists of: (1) an empirical analysis of 54 parallel measurement series to identify the characteristics of the exposure bias in four exposure classes; (2) the development of bias‐estimation models based on an analysis of which variables influence the bias; and (3) the application of the models to an extended version of CRUTEM5 (CRUTEM5_ext), based on exposure metadata, to quantify and reduce the bias. Step one identified differences between the temperatures recorded in Stevenson screens and early exposures, which vary seasonally, diurnally, and with location and exposure class. The largest biases (in mean temperatures) were found in freestanding exposures (up to −0.78°C annually) and in summer, while the smallest biases were generally found in wall‐mounted exposures (near‐0°C annually) and in winter. Significant relationships between the bias and temperature, downward top of atmosphere and/or received shortwave downward solar radiation were found in each exposure class and led to the development of three regression‐based bias‐estimation models. Application of these models to 1,960 mid‐latitude stations in CRUTEM5_ext, resulted in small (≤0.016°C) positive adjustments to the Northern Hemisphere mid‐latitude mean before 1880, and larger (≤−0.1°C) negative adjustments to the Northern and Southern Hemisphere mid‐latitude means between 1882–1934 and 1856–1900, respectively. Larger adjustments were estimated regionally: up to −0.57°C annually and −0.79°C seasonally in individual grid cells.

Cold-induced vasodilation during sequential immersions of the hand - Rebecca S. Weller; Hein A. Daanen; Rebecca J. McClintock; Nicholas A. Roberts; Timothy L. Dunn; Douglas M. Jones (European Journal of Applied Physiology, 2024)
A common practice for those operating in cold environments includes repetitive glove doffing and donning to perform specific tasks, which creates a repetitive cycle of hand cooling and rewarming. This study aimed to determine the influence of intraday repeated hand cooling on cold-induced vasodilation (CIVD), sympathetic activation, and finger/hand temperature recovery. Eight males and two females (mean ± SD age: 28 ± 5 year; height: 181 ± 9 cm; weight: 79.9 ± 10.4 kg) performed two 30-min hand immersions in cold (4.3 ± 0.92 °C) water in an indoor environment (18 °C). Both immersions (Imm1; Imm2) were performed on the same day and both allowed for a 10-min recovery. CIVD components were calculated for each finger (index, middle, ring) during each immersion. CIVD onset time (index, p = 0.546; middle, p = 0.727; ring, p = 0.873), minimum finger temperature (index, p = 0.634; middle, p = 0.493; ring, p = 0.575), and mean finger temperature (index, p = 0.986; middle, p = 0.953; ring, p = 0.637) were all similar between immersions. Recovery rates generally demonstrated similar responses as well. Findings suggest that two sequential CIVD tests analyzing the effect of prior cold exposure of the hand does not impair the CIVD response or recovery. Such findings appear promising for those venturing into cold environments where hands are likely to be repeatedly exposed to cold temperatures.

State of the California Current Ecosystem report in 2022: a tale of two La Niñas - Andrew R. Thompson; Rasmus Swalethorp; Michaela Alksne; Jarrod A. Santora; Elliott L. Hazen; Andrew Leising; Erin Satterthwaite; William J. Sydeman; Clarissa R. Anderson; Toby D. Auth; Simone Baumann-Pickering; Timothy Baumgardner; et al. (Frontiers in Marine Science, 2024)
2022 marked the third consecutive La Niña and extended the longest consecutive stretch of negative Oceanic Niño Index since 1998-2001. While physical and biological conditions in winter and spring largely adhered to prior La Niña conditions, summer and fall were very different. Similar to past La Niña events, in winter and spring coastal upwelling was either average or above average, temperature average or below average, salinity generally above average. In summer and fall, however, upwelling and temperature were generally average or slightly below average, salinity was close to average and chlorophyll a was close to average. Again, as during prior La Niña events, biomass of northern/southern copepods was above/below average off Oregon in winter, and body size of North Pacific krill in northern California was above average in winter. By contrast, later in the year the abundance of northern krill dropped off Oregon while southern copepods increased and body sizes of North Pacific krill fell in northern California. Off Oregon and Washington abundances of market squid and Pacific pompano (indicators of warm, non-typical La Niña conditions) were high. In the 20 th century, Northern anchovy recruitment tended to be high during cold conditions, but despite mostly warm conditions from 2015-2021 anchovy populations boomed and remained high in 2022. Resident seabird reproductive success, which tended in the past to increase during productive La Niña conditions was highly variable throughout the system as common murre and pelagic cormorant, experienced complete reproductive failure at Yaquina Head, Oregon while Brandt’s cormorant reproduction was average. At three sampling locations off central California, however, common murre reproduction was close to or above average while both pelagic and Brandt’s cormorant were above average. California sealion reproduction has been above average each year since 2016, and pup weight was also above average in 2022, likely in response not to La Niña or El Niño but continuous high abundance of anchovy. The highly variable and often unpredictable physical and biological conditions in 2022 highlight a growing recognition of disconnects between basin-scale indices and local conditions in the CCE. “July-December 2022 is the biggest outlier from individual “strong” La Niña (events) ever going back to the 50s.” – Nate Mantua

How we count counts: Examining influences on detection during shoreline surveys of marine debris - Hillary K. Burgess; Timothy T. Jones; Jacqueline K. Lindsey; Carlie E. Herring; Sherry M. Lippiatt; Julia K. Parrish; Amy V. Uhrin (Marine Pollution Bulletin, 2024)

Inhibition of fatty acid binding protein-5 in the basolateral amygdala induces anxiolytic effects and accelerates fear memory extinction - Matthew J. Jones; Taygun C. Uzuneser; Timothy Clement; Hehe Wang; Iwao Ojima; Walter J. Rushlow; Steven R. Laviolette (Psychopharmacology, 2024)

Occurrence and sources of microplastics on Arctic beaches: Svalbard - Tesni Lloyd-Jones; Jonathan J. Dick; Timothy P. Lane; Eoghan M. Cunningham; Konstadinos Kiriakoulakis (Marine Pollution Bulletin, 2023)

Life in the dark: Impact of future winter warming scenarios on carbon and nitrogen cycling in Arctic soils - Maki Miura; Timothy G. Jones; Hilary Ford; Paul W. Hill; Davey L. Jones (Soil Biology and Biochemistry, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

A critical review of microplastics toxicity and potential adverse outcome pathway in human gastrointestinal tract following oral exposure - Lorna R. Jones; Stephanie J. Wright; Timothy W. Gant (Toxicology Letters, 2023)

An assessment of the downstream implications of blood culture collection and transit - Peter J. B. Davies; Timothy P. W. Jones; Mairi Macleod (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Two invasive Hieracium species’ potential distributions within the Greater Yellowstone Ecosystem were defined using invasion susceptibility models and habitat typing - Christie H. Guetling; Lisa C. Jones; Eva K. Strand; Don W. Morishita; Julia Piaskowski; Timothy S. Prather (Biological Invasions, 2023)
Invasive Hieracium plant species are invading the Greater Yellowstone Ecosystem. The potential distribution of orange hawkweed ( Hieracium aurantiacum) and meadow hawkweed ( Hieracium caespitosum) were estimated using habitat susceptibility models to assist land managers’ management of these invasive plants. The objectives of this study were to: (1) develop models describing susceptibility of ecosystems to hawkweed invasion, (2) identify indicator species of orange hawkweed and meadow hawkweed, (3) determine habitat types where these invasive hawkweeds might occur, and (4) create habitat susceptibility maps for management planning and ground surveys. Models were developed using a Mahalanobis distance similarity technique from remotely sensed biotic and abiotic variables, as well as known location data for orange and meadow hawkweed. Ground validation was conducted to assess model weaknesses and subsequent model modification. Indicator plant species were identified as surrogates to determine the likelihood of hawkweed presence during ground survey. Transect data collected from areas susceptible to invasion also were used to determine habitat types where hawkweed might occur. The best model included eight variables: north–south aspect, east–west aspect, slope, NDVI, NDWI, blue spectral band, green spectral band, and precipitation. High susceptibility (65 + % likelihood of suitable habitat) consisted of 66,000 ha for meadow hawkweed and 35,000 ha for orange hawkweed, 5.0% and 2.7% of the study area, respectively. Meadow hawkweed and orange hawkweed had seven and three indicator plant species, respectively. Predicted hawkweed habitat susceptibility encompassed nine habitat types, ranging from xeric sagebrush steppe to wet forests and they overlapped except at the xeric habitat type. Habitat susceptibility models save costs and allow survey prioritization to those areas most susceptible to invasion.

Development of a monoclonal antibody specific to burbot (Lota lota) IgM and optimization of an ELISA to measure anti-Aeromonas sp. antibody titers following pathogen challenge - Luke P. Oliver; Timothy J. Bruce; Jie Ma; Evan M. Jones; Kenneth D. Cain (Fish & Shellfish Immunology, 2023)

Characterization of maternal immunity following vaccination of broodstock against IHNV or Flavobacterium psychrophilum in rainbow trout (Oncorhynchus mykiss) - Jie Ma; Jesse T. Trushenski; Evan M. Jones; Timothy J. Bruce; Doug G. McKenney; Gael Kurath; Kenneth D. Cain (Fish & Shellfish Immunology, 2023)

Estimation of survey efficiency and biomass for commercially important species from industry-based paired gear experiments - Timothy J. Miller; David E. Richardson; Philip J. Politis; Christopher D. Roebuck; John P. Manderson; Michael H. Martin; Andrew W. Jones (Fisheries Research, 2023)

Linking ecosystem services provisioning with demand for animal-sourced food: an integrated modeling study for Tanzania - Dolapo Enahoro; Marta Kozicka; Catherine Pfeifer; Sarah K. Jones; Nhuong Tran; Chin Yee Chan; Timothy B. Sulser; Elisabetta Gotor; Karl M. Rich (Regional Environmental Change, 2023)
Standard tools that can quantitatively track the impacts of higher global demand for animal-sourced food to their local environmental effects in developing countries are largely missing. This paper presents a novel integrated assessment framework that links a model of the global agricultural and food system, a landscape-level environmental impact assessment model, and an ecosystem services simulation model. For Tanzania, this integrated assessment showed that a projected increase in the demand and production of foods of livestock origin with optimistic economic growth between 2010 and 2030 leads to an improvement in food security. However, resulting transitions in land use impact negatively on the future provisioning of ecosystem services, increasing phosphorus, nitrogen, and sediment in runoff and reducing water quality in areas downstream of the agricultural expansion. Losses in ecosystem services are lowest when diversified farming practices are adopted in areas of agricultural land expansion. The role of land management in the environmental impacts of expanded livestock production is highlighted, as is the need for a new generation of analytical tools to inform policy recommendations.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Promoting FAIR Data Through Community-driven Agile Design: the Open Data Commons for Spinal Cord Injury (odc-sci.org) - Abel Torres-Espín; Carlos A. Almeida; Austin Chou; J. Russell Huie; Michael Chiu; Romana Vavrek; Jeff Sacramento; Michael B. Orr; John C. Gensel; Jeffery S. Grethe; Maryann E. Martone; Karim Fouad; et al. (Neuroinformatics, 2022)
The past decade has seen accelerating movement from data protectionism in publishing toward open data sharing to improve reproducibility and translation of biomedical research. Developing data sharing infrastructures to meet these new demands remains a challenge. One model for data sharing involves simply attaching data, irrespective of its type, to publisher websites or general use repositories. However, some argue this creates a ‘data dump’ that does not promote the goals of making data Findable, Accessible, Interoperable and Reusable (FAIR). Specialized data sharing communities offer an alternative model where data are curated by domain experts to make it both open and FAIR. We report on our experiences developing one such data-sharing ecosystem focusing on ‘long-tail’ preclinical data, the Open Data Commons for Spinal Cord Injury (odc-sci.org). ODC-SCI was developed with community-based agile design requirements directly pulled from a series of workshops with multiple stakeholders (researchers, consumers, non-profit funders, governmental agencies, journals, and industry members). ODC-SCI focuses on heterogeneous tabular data collected by preclinical researchers including bio-behaviour, histopathology findings and molecular endpoints. This has led to an example of a specialized neurocommons that is well-embraced by the community it aims to serve. In the present paper, we provide a review of the community-based design template and describe the adoption by the community including a high-level review of current data assets, publicly released datasets, and web analytics. Although odc-sci.org is in its late beta stage of development, it represents a successful example of a specialized data commons that may serve as a model for other fields.

Correction to: Anthropogenic factors influence the occupancy of an invasive carnivore in a suburban preserve system - John P. Vanek; Andrew U. Rutter; Timothy S. Preuss; Holly P. Jones; Gary A. Glowacki (Urban Ecosystems, 2021)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Assessment of Flavobacterium psychrophilum ‐associated mortality in Atlantic salmon ( Salmo salar ) and brook trout ( Salvelinus fontinalis ) - Timothy J. Bruce; Jie Ma; Evan M. Jones; Brent M. Vuglar; Luke P. Oliver; Christopher Knupp; Thomas P. Loch; Kenneth D. Cain (Journal of Fish Diseases, 2021)
Salmonid diseases caused by infections of Flavobacterium psychrophilum , the causative agent of bacterial coldwater disease, remain difficult to manage as novel, pathogenic strains continue to emerge in aquaculture settings globally. To date, much of the research regarding treatment options and vaccine development has focused on rainbow trout ( Oncorhynchus mykiss ), but other inland‐reared salmonids are also impacted by this Gram‐negative bacterium. As such, Atlantic salmon ( Salmo salar ) and brook trout ( Salvelinus fontinalis ) were injection‐challenged with a variety of previously reported F. psychrophilum strains isolated from disease diagnostic cases in salmonids, as well as a standard and well‐studied F. psychrophilum strain (CSF 259–93) known to be virulent in rainbow trout. In three separate virulence assessments (Trials A, B and C), strains US063 (isolated from lake trout; Salvelinus namaycush ) and US149 (isolated from Atlantic salmon) caused a significantly higher cumulative per cent mortality (CPM) relative to other strains in Atlantic salmon ( p p =.008) and B (CPM 96% ± 2.3% vs. 81.33% ± 4.8%, p =.014). Trial C used a lower dose (1.86 × 10 8 CFU/mL) for US149, resulting in a lower mortality (78.67% ± 9.33%) relative to Trials A and B. CSF259‐93 did not cause significant mortality in any trials. In brook trout, the strain 03–179 (originally isolated from steelhead trout; Oncorhynchus mykiss ) was significantly more virulent than any other (CPM 100% ± 0%, p F. psychrophilum virulence testing in Atlantic salmon and brook trout, demonstrating the high virulence of US063 and US149 for these salmonid species. This information is applicable for the development of therapeutics and vaccines against F . psychrophilum infections and demonstrates the reproducibility of the experimental challenge model.

Anthropogenic factors influence the occupancy of an invasive carnivore in a suburban preserve system - John P. Vanek; Andrew U. Rutter; Timothy S. Preuss; Holly P. Jones; Gary A. Glowacki (Urban Ecosystems, 2021)

Isolation and experimental challenge of cultured burbot ( Lota lota maculosa ) with Flavobacterium columnare and Aeromonas sp. isolates - Timothy J. Bruce; Jie Ma; Luke P. Oliver; Evan M. Jones; Benjamin R. LaFrentz; Kenneth D. Cain (Journal of Fish Diseases, 2020)
Burbot ( Lota lota maculosa ) are a potential new species for commercial aquaculture. As burbot culture expands, there is a need to further define pathogen susceptibility and characterize aspects of the burbot immune response in an effort to assess fish health. A recent clinical diagnostic case from juvenile burbot reared at a commercial production facility resulted in the isolation and identification of Flavobacterium columnare along with several Aeromonas spp. The F. columnare isolate was assigned to genetic group 1 via multiplex PCR, a genetic group commonly associated with columnaris disease cases in rainbow trout ( Oncorhynchus mykiss ). Virulence of the F. columnare isolate was assessed in vivo in both juvenile burbot and rainbow trout. Additionally, several of the Aeromonas sp. case isolates were identified via sequencing (16S rRNA, gyrB and rpoD ) and a putative A . sobria isolate (BI‐3) was used to challenge burbot, along with a known virulent Aeromonas sp. (A141), but BI‐3 was not found to be virulent. Burbot were refractory to F. columnare when challenged by immersion, and it is likely that this is a secondary pathogen for burbot. Although refractory in burbot, the identified F. columnare isolate (BI‐1) was found to be virulent in rainbow trout.

Beyond Technical Fixes: climate solutions and the great derangement - Andrea Joslyn Nightingale; Siri Eriksen; Marcus Taylor; Timothy Forsyth; Mark Pelling; Andrew Newsham; Emily Boyd; Katrina Brown; Blane Harvey; Lindsey Jones; Rachel Bezner Kerr; Lyla Mehta; et al. (Climate and Development, 2020)

Dynamics of dissolved organic matter in headwaters: comparison of headwater streams with contrasting DOM and nutrient composition - Ophelie Fovet; David M. Cooper; Davey L. Jones; Timothy G. Jones; Chris D. Evans (Aquatic Sciences, 2020)

Varenicline for cognitive impairment in people with schizophrenia: systematic review and meta-analysis - Timothy Tanzer; Shelukumar Shah; Catherine Benson; Veronica De Monte; Victoria Gore-Jones; Susan L. Rossell; Frances Dark; Steve Kisely; Dan Siskind; Catarina Drumonde Melo (Psychopharmacology, 2020)

Coral Reef Monitoring, Reef Assessment Technologies, and Ecosystem-Based Management - David O. Obura; Greta Aeby; Natchanon Amornthammarong; Ward Appeltans; Nicholas Bax; Joe Bishop; Russell E. Brainard; Samuel Chan; Pamela Fletcher; Timothy A. C. Gordon; Lew Gramer; Mishal Gudka; et al. (Frontiers in Marine Science, 2019)

Inhibition of vascular smooth muscle cell calcification by ATP analogues - Jessal J. Patel; Lucie E. Bourne; José Luis Millán; Timothy R. Arnett; Vicky E. MacRae; Caroline P. D. Wheeler-Jones; Isabel R. Orriss (Purinergic Signalling, 2019)

Population genetic assessment of two critically endangered freshwater mussel species, Tennessee bean Venustaconcha trabalis and Cumberland bean Venustaconcha troostensis - Timothy W. Lane; Eric M. Hallerman; Jess W. Jones (Conservation Genetics, 2019)

Definition of a temporal distribution index for high temporal resolution precipitation data over Peninsular Spain and the Balearic Islands: the fractal dimension; and its synoptic implications - Oliver Meseguer-Ruiz; Timothy J. Osborn; Pablo Sarricolea; Philip D. Jones; Jorge Olcina Cantos; Roberto Serrano-Notivoli; Javier Martin-Vide (Climate Dynamics, 2019)

Dynamics of soil organic carbon following land-use change: insights from stable C-isotope analysis in black soil of Northeast China - Chenglong Tu; Congqiang Liu; Timothy A. Quine; Matthew William Jones; Taoze Liu; Longbo Li; Wenjing Liu (Acta Geochimica, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Continuous human presence without extensive reductions in forest cover over the past 2500 years in an aseasonal Amazonian rainforest - Thomas J. Kelly; Ian T. Lawson; Katherine H. Roucoux; Timothy R. Baker; Euridice N. Honorio‐Coronado; Timothy D. Jones; Santiago Rivas Panduro (Journal of Quaternary Science, 2018)
The impact of pre‐Columbian indigenous communities on forest cover in Amazonia is highly contentious, particularly for the wettest forests. To contribute to this debate, we studied the vegetation and fire history of a site, Quistococha, which lies within the aseasonal forests of the northern Peruvian Amazon and is associated with independently dated pre‐Columbian and recent human occupation. Paired cores from swamp and lake environments were used to distinguish landscape‐scale changes in vegetation from local‐scale succession. An increased abundance of disturbance‐adapted taxa in the pollen record from the lake, but not swamp, since c . AD 1860 probably reflects extensive deforestation related to the expansion of the nearby city of Iquitos. However, previous persistent occupation of the site by pre‐Columbian indigenous communities, indicated by the charcoal record from the lake site, is not associated with evidence for similarly extensive disturbance of the landscape. The unique features of this site therefore demonstrate that occupation by indigenous communities over thousands of years was not associated with large‐scale deforestation. These results support an emerging model of persistent but localized impacts by pre‐Columbian indigenous communities on aseasonal Amazonian forests.

Negative allosteric modulation of alpha 5-containing GABAA receptors engenders antidepressant-like effects and selectively prevents age-associated hyperactivity in tau-depositing mice - Nina Z. Xu; Margot Ernst; Marco Treven; Rok Cerne; Mark Wakulchik; Xia Li; Timothy M. Jones; Scott D. Gleason; Denise Morrow; Jeffrey M. Schkeryantz; Md. Toufiqur Rahman; Guanguan Li; et al. (Psychopharmacology, 2018)

Predicted environmental concentration and fate of the top 10 most dispensed Australian prescription pharmaceuticals - Timothy T. X. Ong; Ewan W. Blanch; Oliver A. H. Jones (Environmental Science and Pollution Research, 2018)

Potential pesticides for control of a recently introduced ambrosia beetle (Euwallacea sp.) in southern California - Michele Eatough Jones; Timothy D. Paine (Journal of Pest Science, 2018)

Climate Variability and Change: Response of a Coastal Ocean Ecosystem - Francisco Chavez; J. Timothy Pennington; Reiko Michisaki; Marguerite Blum; Gabriela Chavez; Jules Friederich; Brent Jones; Robert Herlien; Brian Kieft; Brett Hobson; Alice Ren; John Ryan; et al. (Oceanography, 2017)

Natriuretic peptide activation of extracellular regulated kinase 1/2 (ERK1/2) pathway by particulate guanylyl cyclases in GH3 somatolactotropes - Kim C. Jonas; Timothy Melrose; Iain R. Thompson; Gary F. Baxter; Victoria J. Lipscomb; Stijn J. Niessen; Charlotte Lawson; Craig A. McArdle; Mark S. Roberson; Imelda M. McGonnell; Caroline P. Wheeler-Jones; Robert C. Fowkes (Cell and Tissue Research, 2017)

Effective radiative forcing from historical land use change - Timothy Andrews; Richard A. Betts; Ben B. B. Booth; Chris D. Jones; Gareth S. Jones (Climate Dynamics, 2017)

Enhancement of wildlife disease surveillance using multiplex quantitative PCR: development of qPCR assays for major pathogens in UK squirrel populations - Timothy D. Dale; Phillip C. Watts; David Jones; Kieran Pounder; David J. Everest; Michael E. Begon; Julian Chantrey (European Journal of Wildlife Research, 2016)

Phylogenetic and taxonomic assessment of the endangered Cumberland bean, Villosa trabalis and purple bean, Villosa perpurpurea (Bivalvia: Unionidae) - Timothy W. Lane; E. M. Hallerman; J. W. Jones (Conservation Genetics, 2016)

Transformations in DOC along a source to sea continuum; impacts of photo-degradation, biological processes and mixing - Timothy G. Jones; Chris D. Evans; Davey L. Jones; Paul W. Hill; Chris Freeman (Aquatic Sciences, 2016)

The greenhouse gas (GHG) emissions associated with aquatic carbon removal during drinking water treatment - Timothy G. Jones; Chris D. Evans; Chris Freeman (Aquatic Sciences, 2016)

Plant Species Effects on the Carbon Storage Capabilities of a Blanket bog Complex - Christian Dunn; Timothy Graham Jones; Sally Roberts; Chris Freeman (Wetlands, 2016)

The Feasibility and Educational Value of Hear My Voice, a Chaplain-Led Spiritual Life Review Process for Patients with Brain Cancers and Progressive Neurologic Conditions - Katherine M. Piderman; Carmen Radecki Breitkopf; Sarah M. Jenkins; Laura A. Lovejoy; Yvette M. Dulohery; Dean V. Marek; Heidi L. Durland; Debra L. Head; Spence W. Swanson; James T. Hogg; John L. Evans; Scott E. Jorgenson; et al. (Journal of Cancer Education, 2015)

Vestibular dysfunction, altered macular structure and trait localization in A/J inbred mice - Sarath Vijayakumar; Teresa E. Lever; Jessica Pierce; Xing Zhao; David Bergstrom; Yunxia Wang Lundberg; Timothy A. Jones; Sherri M. Jones (Mammalian Genome, 2015)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

The Geochemistry of Amazonian Peats - Ian T. Lawson; Timothy D. Jones; Thomas J. Kelly; Euridice N. Honorio Coronado; Katherine H. Roucoux (Wetlands, 2014)

Field phenotyping of potato to assess root and shoot characteristics associated with drought tolerance - Jane Wishart; Timothy S. George; Lawrie K. Brown; Philip J. White; Gavin Ramsay; Hamlyn Jones; Peter J. Gregory (Plant and Soil, 2014)

Methodologies for Extracellular Enzyme Assays from Wetland Soils - Christian Dunn; Timothy G. Jones; Astrid Girard; Chris Freeman (Wetlands, 2014)

Acute hyperglycaemia does not alter nitric oxide-mediated microvascular function in the skin of adolescents with type 1 diabetes - Louise H. Naylor; Norhaida M. Yusof; Nirubasini Paramalingam; Timothy W. Jones; Elizabeth A. Davis; Daniel J. Green (European Journal of Applied Physiology, 2014)

Enhancing the relevance of Shared Socioeconomic Pathways for climate change impacts, adaptation and vulnerability research - Bas J. van Ruijven; Marc A. Levy; Arun Agrawal; Frank Biermann; Joern Birkmann; Timothy R. Carter; Kristie L. Ebi; Matthias Garschagen; Bryan Jones; Roger Jones; Eric Kemp-Benedict; Marcel Kok; et al. (Climatic Change, 2014)

Isolation and characterization of 18 novel polymorphic microsatellite markers from the Mayan cichlid (Cichlasoma urophthalmus) - Elizabeth Harrison; Cara N. Love; Kenneth L. Jones; Stacey L. Lance; Joel C. Trexler; Timothy Collins (Conservation Genetics Resources, 2013)

Could some coral reefs become sponge reefs as our climate changes? - James J. Bell; Simon K. Davy; Timothy Jones; Michael W. Taylor; Nicole S. Webster (Global Change Biology, 2013)
Coral reefs across the world have been seriously degraded and have a bleak future in response to predicted global warming and ocean acidification ( OA ). However, this is not the first time that biocalcifying organisms, including corals, have faced the threat of extinction. The end‐Triassic mass extinction (200 million years ago) was the most severe biotic crisis experienced by modern marine invertebrates, which selected against biocalcifiers; this was followed by the proliferation of another invertebrate group, sponges. The duration of this sponge‐dominated period far surpasses that of alternative stable‐ecosystem or phase‐shift states reported on modern day coral reefs and, as such, a shift to sponge‐dominated reefs warrants serious consideration as one future trajectory of coral reefs. We hypothesise that some coral reefs of today may become sponge reefs in the future, as sponges and corals respond differently to changing ocean chemistry and environmental conditions. To support this hypothesis, we discuss: (i) the presence of sponge reefs in the geological record; (ii) reported shifts from coral‐ to sponge‐dominated systems; and (iii) direct and indirect responses of the sponge holobiont and its constituent parts (host and symbionts) to changes in temperature and pH . Based on this evidence, we propose that sponges may be one group to benefit from projected climate change and ocean acidification scenarios, and that increased sponge abundance represents a possible future trajectory for some coral reefs, which would have important implications for overall reef functioning.

Altered calsequestrin glycan processing is common to diverse models of canine heart failure - Sony Jacob; Naama H. Sleiman; Stephanie Kern; Larry R. Jones; Javier A. Sala-Mercado; Timothy P. McFarland; Hani H. Sabbah; Steven E. Cala (Molecular and Cellular Biochemistry, 2013)

Methane indicator values for peatlands: a comparison of species and functional groups - Alan Gray; Peter E. Levy; Mark D. A. Cooper; Timothy Jones; Jenny Gaiawyn; Sarah R. Leeson; Susan E. Ward; Kerry J. Dinsmore; Julia Drewer; Lucy J. Sheppard; Nick J. Ostle; Chris D. Evans; et al. (Global Change Biology, 2013)
Previous studies have shown a correspondence between the abundance of particular plant species and methane flux. Here, we apply multivariate analyses, and weighted averaging, to assess the suitability of vegetation composition as a predictor of methane flux. We developed a functional classification of the vegetation, in terms of a number of plant traits expected to influence methane production and transport, and compared this with a purely taxonomic classification at species level and higher. We applied weighted averaging and indirect and direct ordination approaches to six sites in the United Kingdom, and found good relationships between methane flux and vegetation composition (classified both taxonomically and functionally). Plant species and functional groups also showed meaningful responses to management and experimental treatments. In addition to the United Kingdom, we applied the functional group classification across different geographical regions (Canada and the Netherlands) to assess the generality of the method. Again, the relationship appeared good at the site level, suggesting some general applicability of the functional classification. The method seems to have the potential for incorporation into large‐scale (national) greenhouse gas accounting programmes (in relation to peatland condition/management) using vegetation mapping schemes. The results presented here strongly suggest that robust predictive models can be derived using plant species data (for use in national‐scale studies). For trans‐national‐scale studies, where the taxonomic assemblage of vegetation differs widely between study sites, a functional classification of plant species data provides an appropriate basis for predictive models of methane flux.

Diatom-inferred late Pleistocene and Holocene palaeolimnological changes in the Ioannina basin, northwest Greece - Timothy D. Jones; Ian T. Lawson; Jane M. Reed; Graham P. Wilson; Melanie J. Leng; Merle Gierga; Stefano M. Bernasconi; Rienk H. Smittenberg; Irka Hajdas; Charlotte L. Bryant; P. C. Tzedakis (Journal of Paleolimnology, 2013)

Estimates of the North Atlantic Oscillation back to 1692 using a Paris–London westerly index - Richard C. Cornes; Philip D. Jones; Keith R. Briffa; Timothy J. Osborn (International Journal of Climatology, 2013)
A westerly index for Europe is developed back to 1692 using newly recovered and corrected Mean Sea‐level Pressure (MSLP) data from London and Paris. The index is compared against various instrumental and proxy indices of the North Atlantic Oscillation (NAO). In the winter, the Paris‐London index depicts a spatial pattern of atmospheric circulation that is bi‐modal, with centres of action that are shifted eastwards compared to the NAO. Owing to asymmetry in the NAO the Paris‐London index provides a good depiction of positive NAO conditions as well as extreme negative phases of the NAO that arise from reversals of the pressure centres, but less extreme negative NAO conditions are associated with westerly index values approaching zero. The merit in using the Paris‐London index lies with its consistency over time as a measure of westerly wind flow, which may not be the case with other proxy‐based indices. In the summer, the Paris‐London index bears a close relationship to the reconstructed high‐summer NAO series of Folland et al. ( 2009 ) as well as the summer Luterbacher et al. ( 1999 ) NAO reconstruction. An important finding is that the summer NAO was highly variable during the early nineteenth century but was predominately positive on the decadal time scale during that period. Since circa 1970 the summer index has mostly been negative, indicating reduced westerlies and increased blocking conditions that are exceptional in the context of the last 250 years. Copyright © 2012 Royal Meteorological Society

A daily series of mean sea‐level pressure for Paris, 1670–2007 - Richard C. Cornes; Phil D. Jones; Keith R. Briffa; Timothy J. Osborn (International Journal of Climatology, 2012)
It has been known for some time that the potential exists to construct a long daily series of surface pressure for the city of Paris because of the existence of various instrumental series that might be pieced together. The remarkable weather diary kept by the physician, Louis Morin, sets the start of the potential series to 1670, and various other series have now been digitized and corrected to allow the formation of a daily series of Mean Sea‐Level Pressure (MSLP) that spans the greater part of 300 years. Unfortunately, a gap in the series still exists for the period 1726–1747, where it appears that no barometer observations have survived. This paper discusses the sources of the various pressure data used in the Paris daily MSLP series, and describes how these observations have been corrected and amalgamated to form a near‐continuous, homogeneous series. The data are compared with a similar long daily series that has been independently constructed for the city of London (1692–2007). This comparison indicates that the two MSLP series are of a sufficient quality to provide useful information about the atmospheric circulation across western Europe over the last 300 years. Copyright © 2011 Royal Meteorological Society

Ants impact sawfly oviposition on bracken fern in southern California - Michele Eatough Jones; Timothy D. Paine (Arthropod-Plant Interactions, 2012)

Are Any Coastal Internal Tides Predictable? - Jonathan Nash; Emily Shroyer; Samuel Kelly; Mark Inall; Timothy Duda; Murray Levine; Nicole Jones; Ruth Musgrave (Oceanography, 2012)

Methane emissions from soils: synthesis and analysis of a large UK data set - Peter E. Levy; Annette Burden; Mark D. A. Cooper; Kerry J. Dinsmore; Julia Drewer; Chris Evans; David Fowler; Jenny Gaiawyn; Alan Gray; Stephanie K. Jones; Timothy Jones; Niall P. McNamara; et al. (Global Change Biology, 2012)
Nearly 5000 chamber measurements of CH 4 flux were collated from 21 sites across the U nited K ingdom, covering a range of soil and vegetation types, to derive a parsimonious model that explains as much of the variability as possible, with the least input requirements. Mean fluxes ranged from −0.3 to 27.4 nmol CH 4 m −2 s −1 , with small emissions or low rates of net uptake in mineral soils (site means of −0.3 to 0.7 nmol m −2 s −1 ) and much larger emissions from organic soils (site means of −0.3 to 27.4 nmol m −2 s −1 ). Less than half of the observed variability in instantaneous fluxes could be explained by independent variables measured. The reasons for this include measurement error, stochastic processes and, probably most importantly, poor correspondence between the independent variables measured and the actual variables influencing the processes underlying methane production, transport and oxidation. When temporal variation was accounted for, and the fluxes averaged at larger spatial scales, simple models explained up to ca. 75% of the variance in CH 4 fluxes. Soil carbon, peat depth, soil moisture and pH together provided the best sub‐set of explanatory variables. However, where plant species composition data were available, this provided the highest explanatory power. Linear and nonlinear models generally fitted the data equally well, with the exception that soil moisture required a power transformation. To estimate the impact of changes in peatland water table on CH 4 emissions in the U nited K ingdom, an emission factor of +0.4 g CH 4 m −2 yr −1 per cm increase in water table height was derived from the data.

A daily series of mean sea‐level pressure for London, 1692–2007 - Richard C. Cornes; Phil D. Jones; Keith R. Briffa; Timothy J. Osborn (International Journal of Climatology, 2012)
This paper presents a new 300‐year daily series of Mean Sea‐Level Pressure (MSLP) for the city of London. Daily barometer readings recorded in the vicinity of London were digitised from several sources and by joining these data with previously available data, a near‐continuous series was constructed to span the period 1692–2007. The data were quality controlled and then corrected to represent daily means of MSLP at standard modern‐day conditions. This series was then subjected to a statistical homogenisation procedure. The Penalized Maximal t ‐test was used with several reference series to identify breakpoints in the series over the period 1780–2007. In the absence of suitable reference series, the homogeneity of the earlier 1692–1779 period was tested using the Penalized Maximal F‐test. Both tests were implemented through the RHtestV2 software on the monthly and annual means derived from the daily data. The majority of the identified breakpoints could be supported by meta‐data and most occur at the juncture of the component series. A major feature of the homogenised series is that the long‐term mean is 1.2 hPa lower than that of the previous monthly series for London created under the EU ADVICE project for the period 1774–1999. The long‐term mean of 1015.2 hPa for the new series is more consistent with other long MSLP series in the UK. Copyright © 2011 Royal Meteorological Society

Pacific Rim Forestry - Thomas Brandeis; Olaf Kuegler; Robert Pattison; Örjan Jonsson; James Halperin; Kathleen McGinely; Constance Carpenter; Kathleen Friday; Guy Robertson; Nicklos Dudley; Robert James; Richard Sniezko; et al. (Journal of Forestry, 2011)
68Stakeholders' questions about subtropical and tropical forests can be as diverse and unique as the forests themselves. Obtaining the information needed to begin answering these questions requires innovation and adaptation of existing forest mensuration and inventory techniques that were developed primarily for use in temperate and boreal forests with a strong forest industry presence. Five cycles of forest inventory and monitoring in Puerto Rico and two cycles in the US Virgin Islands under the Forest Inventory and Analysis (FIA) program highlight the commonalities and differences between working in these subtropical forests and the temperate forests of the continental United States. Additionally, the Caribbean implementation of the FIA program has often taken a different approach from that used in the Pacific Islands territories. We can improve on delivery of forest resource information to island stakeholders by studying these experiences. By sharing the lessons learned with other Pacific Rim countries engaging in forest inventory and monitoring, we can learn from each other.

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.

Erratum to: Establishment of Psyllaephagus parvus and P. perplexus as serendipitous biological control agents of Eucalyptus psyllids in southern California - Michele Eatough Jones; Kent M. Daane; Timothy D. Paine (BioControl, 2011)

Establishment of Psyllaephagus parvus and P. perplexans as serendipitous biological control agents of Eucalyptus psyllids in southern California - Michele Eatough Jones; Kent M. Daane; Timothy D. Paine (BioControl, 2011)

The effect of nitrogen additions on bracken fern and its insect herbivores at sites with high and low atmospheric pollution - Michele Eatough Jones; Mark E. Fenn; Timothy D. Paine (Arthropod-Plant Interactions, 2011)

Trophic level asynchrony in rates of phenological change for marine, freshwater and terrestrial environments - STEPHEN J. THACKERAY; TIMOTHY H. SPARKS; MORTEN FREDERIKSEN; SARAH BURTHE; PHILIP J. BACON; JAMES R. BELL; MARC S. BOTHAM; TOM M. BRERETON; PAUL W. BRIGHT; LAURENCE CARVALHO; TIM CLUTTON‐BROCK; ALISTAIR DAWSON; et al. (Global Change Biology, 2010)
Recent changes in the seasonal timing (phenology) of familiar biological events have been one of the most conspicuous signs of climate change. However, the lack of a standardized approach to analysing change has hampered assessment of consistency in such changes among different taxa and trophic levels and across freshwater, terrestrial and marine environments. We present a standardized assessment of 25 532 rates of phenological change for 726 UK terrestrial, freshwater and marine taxa. The majority of spring and summer events have advanced, and more rapidly than previously documented. Such consistency is indicative of shared large scale drivers. Furthermore, average rates of change have accelerated in a way that is consistent with observed warming trends. Less coherent patterns in some groups of organisms point to the agency of more local scale processes and multiple drivers. For the first time we show a broad scale signal of differential phenological change among trophic levels; across environments advances in timing were slowest for secondary consumers, thus heightening the potential risk of temporal mismatch in key trophic interactions. If current patterns and rates of phenological change are indicative of future trends, future climate warming may exacerbate trophic mismatching, further disrupting the functioning, persistence and resilience of many ecosystems and having a major impact on ecosystem services.

Variability in the spatial association patterns of sponge assemblages in response to environmental heterogeneity - James J. Bell; Jade Berman; Timothy Jones; Leanne J. Hepburn (Marine Biology, 2010)

Ecophysiological responses of salt cedar (Tamarix spp. L.) to the northern tamarisk beetle (Diorhabda carinulata Desbrochers) in a controlled environment - Keirith A. Snyder; Shauna M. Uselman; Timothy J. Jones; Sara Duke (Biological Invasions, 2010)

What tissue bankers should know about the use of allograft heart valves - David J. Barron; Natasha E. Khan; Timothy J. Jones; Robert G. Willets; William J. Brawn (Cell and Tissue Banking, 2010)

Influence of typhoons on annual CO 2 flux from a subtropical, humic lake - STUART E. JONES; TIMOTHY K. KRATZ; CHIH‐YU CHIU; KATHERINE D. McMAHON (Global Change Biology, 2009)
The Intergovernmental Panel on Climate Change predicts dramatic changes in precipitation patterns over the next century. One potential method for inferring how these changes in annual precipitation and intensity of storm events will influence aquatic ecosystems is to study and model present‐day lakes that share climatic characteristics with future climate scenarios. A small lake in north‐central Taiwan provided an excellent opportunity to explore the influence of intense meteorological events on CO 2 exchange between surface waters and the atmosphere. Each year Yuan Yang Lake (YYL) is influenced by multiple typhoons that pass near the island of Taiwan. This lake has been instrumented with a sensor network that monitors water column and meteorological parameters at a high temporal resolution (2–10 min intervals). Using this high‐resolution data and manually collected CO 2 samples, a mass‐balance model of CO 2 dynamics in YYL was developed. In addition, a generalized simulation model was used to explore how typhoon frequency, intensity, and timing impact CO 2 efflux to the atmosphere. Our findings suggest that increased annual precipitation and frequency of storm events results in greater epilimnetic interaction with the watershed and hypolimnion. These interactions resulted in elevated epilimetic CO 2 concentrations and therefore greater evasion of CO 2 to the atmosphere.

Typhoons initiate predictable change in aquatic bacterial communities - Stuart E. Jones; Chih-Yu Chiu; Timothy K. Kratz; Jiunn-Tzong Wu; Ashley Shade; Katherine D. McMahon (Limnology and Oceanography, 2008)
We explored patterns of change in bacterioplankton and phytoplankton community composition in response to typhoons in a subtropical, subalpine freshwater humic lake in Taiwan. Thermal profiles with depth, nearsurface dissolved oxygen, and meteorological conditions were measured at high temporal resolution using an instrumented buoy. We collected samples across a time series spanning two typhoon seasons and assessed bacterial community composition at each time point using a fingerprinting technique targeting the internal transcribed spacer region of the ribosomal RNA operon. Wind and rain associated with the typhoons mixed the otherwise stably stratified water column. After each of six typhoon‐induced mixing events, the bacterial community composition was reset to similar conditions, revealing a surprisingly deterministic pattern of recovery that was reminiscent of secondary succession following large infrequent disturbances in terrestrial ecosystems. Distinct bacterial assemblages were associated with epilimnion and hypolimnion samples collected more than 80 d after a mixing event. These assemblages were also distinct from the communities observed in the generally unstratified water column within 7 d after a typhoon. Our results were surprising since bacterial communities are not expected to respond in such predictable ways because of their immense complexity and diversity. In contrast, phytoplankton communities did not recover in a predictable way after typhoons.

Impaired exercise ventilatory mechanics with the self-contained breathing apparatus are improved with heliox - Scott J. Butcher; Richard L. Jones; Jonathan R. Mayne; Timothy C. Hartley; Stewart R. Petersen (European Journal of Applied Physiology, 2007)

The impact of natural and anthropogenic forcings on climate and hydrology since 1550 - Simon F. B. Tett; Richard Betts; Thomas J. Crowley; Jonathan Gregory; Timothy C. Johns; Andy Jones; Timothy J. Osborn; Elisabeth Öström; David L. Roberts; Margaret J. Woodage (Climate Dynamics, 2006)

Molecular approach for assessing responses of microbial‐feeding nematodes to burning and chronic nitrogen enrichment in a native grassland - KENNETH L. JONES; TIMOTHY C. TODD; JULIE L. WALL‐BEAM; JOSEPH D. COOLON; JOHN M. BLAIR; MICHAEL A. HERMAN (Molecular Ecology, 2006)
A substantial proportion of the primary productivity in grassland ecosystems is allocated belowground, sustaining an abundant and diverse community of microbes and soil invertebrates. These belowground communities drive many important ecosystem functions and are responsive to a variety of environmental changes. Nematodes, an abundant and diverse component of grassland soil communities, are particularly responsive to altered environmental conditions, such as those associated with reduced fire frequency and nitrogen enrichment, with the most consistent responses displayed by microbial‐feeding nematodes. However, much of the available research characterizing nematode responses to environmental change has been carried out at the taxonomic level of family or by broad trophic categories (e.g. fungivores, bacterivores). The extent to which differential responses to environmental change occurs at the genus level or below is unclear. Therefore, the objective of this study was to use molecular methods to quantify the response of microbial‐feeding nematodes, at the lowest levels of taxonomic resolution, to nitrogen enrichment and changes in fire frequency. Using sequencing and quantitative polymerase chain reaction (PCR) probes for the 18S ribosomal RNA gene and the ITS1 region, we identified 19 microbial‐feeding nematode taxa across four families. When nematodes were sampled across treatments, we found that some nematode taxa within a family responded similarly to nitrogen and burning treatments, while other taxa within the same family respond quite differently. Additionally, although nematodes from different families on average responded differently to nitrogen enrichment and burning, similar responses were seen in nematode taxa that span three taxonomic families. Thus, if nematodes are to be used as indicators of environmental change, care should be taken to assess the response at the lowest taxonomic level possible.

An improved method of constructing a database of monthly climate observations and associated high-resolution grids - Timothy D. Mitchell; Philip D. Jones (International Journal of Climatology, 2005)

Transformation of alternan-producing strains of Leuconostoc by electroporation - Timothy D. Leathers; James D. Jones; Herb A. Wyckoff (Biotechnology Letters, 2004)

Spatial, temporal and size-class variation in the diet of estuary perch (Macquaria colonorum) in the Hopkins River, Victoria, Australia - Timothy Howell; Laurie Jon Laurenson; Jackie H. Myers; Paul L. Jones (Hydrobiologia, 2004)

Sequence variation in the CHAT locus shows no association with late-onset Alzheimer's disease - Denise Harold; Timothy Peirce; Valentina Moskvina; Simon Lovestone; John Powell; Catherine Foy; Nicola Archer; Sarah Walter; Amanda Edmonson; Stephen McIlroy; David Craig; Peter A. Passmore; et al. (Human Genetics, 2003)

Clonus after human spinal cord injury cannot be attributed solely to recurrent muscle-tendon stretch - Janell A. Beres-Jones; Timothy D. Johnson; Susan J. Harkema (Experimental Brain Research, 2003)

Fragmentation of Continental United States Forests - Kurt H. Riitters; James D. Wickham; Robert V. O'Neill; K. Bruce Jones; Elizabeth R. Smith; John W. Coulston; Timothy G. Wade; Jonathan H. Smith (Ecosystems, 2002)

The Collection of PM10 for Toxicological Investigation: Comparisons between Different Collecting Devices - Leona L. Greenwell; Timothy P. Jones; Roy J. Richards (Environmental Monitoring and Assessment, 2002)

Assessing Landscape Condition Relative to Water Resources in the Western United States: A Strategic Approach - K. Bruce Jones; Daniel T. Heggem; Timothy G. Wade; Anne C. Neale; Donald W. Ebert; Maliha S. Nash; Megan H. Mehaffey; Karl A. Hermann; Anthony R. Selle; Scott Augustine; Iris A. Goodman; Joel Pedersen; et al. (Environmental Monitoring and Assessment, 2000)

Observed trends in the daily intensity of United Kingdom precipitation - Timothy J. Osborn; Mike Hulme; Philip D. Jones; Tracy A. Basnett (International Journal of Climatology, 2000)

New immunodiagnostic system - Euan R. Tovey; David J.M. Taylor; Anthony H. Graham; Timothy J. O'Meara; Uffe Lovborg; Allan Jones; Richard Sporik (Aerobiologia, 2000)

Evaluating Change in Rangeland Condition using Multitemporal AVHRR Data and Geographic Information System Analysis - Timothy B. Minor; Judith Lancaster; Timothy G. Wade; James D. Wickham; Walter Whitford; K. Bruce Jones (Environmental Monitoring and Assessment, 1999)

Molecular cytogenetic characterization of Thinopyrum and wheat--Thinopyrum translocated chromosomes in a wheat--Thinopyrum amphiploid - Xiwen Cai; Stephen S. Jones; Timothy D. Murray (Chromosome Research, 1998)

Characterization of tetraploid wheat germplasm for resistance to Pseudocercosporella herpotrichoides, cause of eyespot disease - Giovanni Figliuolo; Stephen S. Jones; Timothy D. Murray; Peir Luigi Spagnoletti Zeuli (Genetic Resources and Crop Evolution, 1998)

Short latency vestibular evoked potentials in the Japanese quail ( Coturnix coturnix japonica ) - Sherri M. Jones; Timothy A. Jones; Roshni Shukla (Journal of Comparative Physiology A, 1997)